METACOGNITIVE SKILLS IN MATHEMATICS PROBLEM SOLVING - Lestari, Wahyu; Jailani, Jailani; Pratama, Loviga (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2018)
This study is a descriptive qualitative approach. The purpose of this study was to describe level metacognitive skills of students in solving the problem solving test item based on indicators that had been compiled. Metacognitive skills in this study form planning, monitoring, reflection aspect. Data analysis aimed to describe the students’ metacognitive skills. Then, the researcher categorized the students’ metacognitive skills into reflective use, strategic use, aware use, and tacit use. The data collection methods in this study were documentation, test, and interview. From 40 student spread across many Junior High Schools in Jember district, 8 students are found to be able reading and writing of what was known (P-1), determining solving strategies (P-2), Using rules (M-1), and monitoring carefully (M-2), thus classified as having metacognitive skills into aware use. Furthermore, 20 students are able to perform (P-1), (P-2), planning intermediate results (P-3), (M-1), (M-2), able to correct mistake (M-3), and Reflecting achievement of the objectives (R-1), thus classified as having metacognitive skills into strategic use. Furthermore, 12 students are able to perform (P-1), (P-2), (P-3), (M-1), (M-2), (M-3), (R-1), do wareness on the application/use of strategies (R-2), analyze the text/formula (R-3), choosing intentionally the representation (R-4), thus classified as having metacognitive skills into reflective use